เจ็ตที่หมุดควงในกระแสลมขวาง : การศึกษาด้วยโฟลวิชชวลไลเซชัน - ปราโมทย์ ลิ้มดำรงธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Characteristics and mixed fluid structures of a jet in crossflow (JICF) and swirling jets in crossflow (SJICF) with non-zero tangential velocity and non-zero circulation (NZT/NZC) are experimentally investigated by means of Product formation/Mie scattering/Laser-sheet imaging technique. In the experiment, smoke fluid is introduced into the hot air jet, and evaporated, upstream of the jet exit. When the mixture jet is issued at the jet exit, it entrains and mixes with cold crossflow air, resulting in the smoke fluid vapor condensing to small aerosol particles that mark the regions of mixed fluid. The mixed fluid structures are then imaged with a laser sheet and a CCD camera. The experiment is conducted at the jet in crossflow effective velocity ratio of 4.13, the jet Reynolds number of 14,000, the crossflow Reynolds number of 4,600. Three swirl ratios (Sr) are investigated, namely 0 (JICF), 0.5, and 0.8. The mixed fluid structures are imaged in three sets of perpendicular cross sectional planes, namely the cross sectional planes in the top, end, and side views. In the case of JICF, instantaneous image in the top view reveals a series of small Kelvin-Helmholtz (K-H) azimuthal structures of mixed fluid (which appear as bright structures) cascading azimuthally around the unmixed core of the jet (which appears as a dark region) very near the jet exit (e.g., at y/rd = 0.05). In addition, it also reveals a more developed and larger K-H vortical roll-up structure that periodically shedding from each lateral side of the jet. While these structures can be observed in instantaneous image early on near the jet exit, the series of small K-H azimuthal structures cannot be observed in the mean image due to the averaging and the more developed K-H structure at each lateral side will not be observed in the mean image until some further distance downstream (e.g., at y/rd = 0.15). From the end view, instantaneous image reveals vortical roll-ups at each lateral side near the jet exit. Furthermore, the mean image shows mixed fluid to be concentrated more on each lateral and lower part of the jet. With the unmixed core at the center, the cross section of the mean mixed fluid structure in the near field from this end view appears to be horseshoe in shape. As the jet develops further downstream, the mean mixed fluid structure evolves into the counter-rotating vortex pairs (CVP). In the case of SJICF, instantaneous image in the top view reveals similar series of small K-H azimuthal structures of mixed fluid around the unmixed core and the more developed K-H vortical roll-up as before, but this time the amount of mixed fluid and the structures are obviously biased towards the pressure side in comparison to the suction side. Of particular note is the much larger K-H roll-up and shedding on the pressure side in the near field. In addition, when the mean and standard deviation images are considered, more mixed fluid and local peak, and high turbulent intensity are found on the pressure side. From the end view, similar vortical roll-ups as in JICF are observed in instantaneous image, but again the bias is towards the pressure side; more mixed fluid and larger vortical structures are found on this side. The mean and standard deviation images also show similar trend. Furthermore, it is found that swirl causes lower jet trajectory and shorter unmixed core. Finally, better mixing on the pressure side in comparison to the suction side in the case of NZT/NZC SJICF is attributed to the initial tangential velocity profile. Specifically, this type of initial tangential velocity profile results in shear layer with larger strength along the pressure side, making the vortical structures on this side being more effective in entraining crossflow fluid as well as promoting turbulence for mixing along this side.